Caracterização genético-populacional de Prochilodus nigricans (Prochilodontidae) na sub-bacia do rio Tapajós - Lopes, Ueslei da Conceição (Universidade Federal de São Carlos, 2018)
Prochilodus nigricans is a migratory detritivorous fish, with a silvery grey colored body and dark, irregular, wavy, bar-like patterns on the caudal-fin lobes. This species is widely distributed in the Amazon and Tocantins river basins and stands out for its great economic importance and social relevance due to subsistence fisheries. Because of the uncertainties recently raised regarding the validity of the species, the aims of this work were to access the genetic diversity of P. nigricans in the region of the Brazilian shield and to characterize the genetic-population parameters of this species in the sub-basin of the Tapajós river during a nonreproductive period. In order to test the occurrence of hidden diversity, we used the mitochondrial markers COI and ATP6/8 in samples from the Tapajós, Xingu and TocantinsAraguaia sub-basins, and conducted a GMYC analysis with COI, considering the sequences generated in the present study and Genbank sequences of individuals sampled in other regions of the Amazon basin. Population structure and genetic diversity analyzes were performed using eight microsatellite loci and, the ATP6/8 genes and the mitochondrial DNA control region. For both COI and ATP6/8, there was a significant divergence between individuals sampled in the Tapajós river, with genetic distance values ranging from 1% to 1.9% between this group and the other individuals sampled in the Brazilian shield. The GMYC analysis identified that these individuals constitute another MOTU (molecular operational taxonomic unit), which were excluded from the population analyzes conducted in the Tapajós sub-basin. Mitochondrial and microsatellite data evidenced three genetically differentiated populations, Tapajós, Teles Pires and Juruena, the latter of which was genetically more differentiated. The three evaluated populations presented high and similar genetic diversity values to those of other species of Prochilodus and showed no signs of population expansion or decline in the last 200 thousand years. The results obtained in the present study on the diversity of P. nigricans are of particular relevance, since they make possible a previous diagnosis of the genetic status of P. nigricans populations in the tributaries and the main channel of the Tapajós river, before the eventual effects caused by the implantation of dams. Such data will serve as a basis for future studies to evaluate the impact of these constructions on the distribution pattern of the genetic diversity of migratory species, serving as an important tool to observe changes in the genetic structure of populations in areas fragmented by dams, and to subsidize management programs that aim at the conservation of the ichthyofauna in these regions.
Genetic structure of Prochilodus nigricans (Prochilodontidae) in the Tapajós river sub-basin
Caracterización genético-poblacional de Prochilodus nigricans (Prochilodontidae) en la subcuenca del río Tapajós
Keywords: Conservação; Genética de populações; Bocachico; Curimbatá; Conservation; Population genetics; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL